Matematika dalam Multimedia Flipbook: Kreatifitas Guru dalam Pengembangan Media Pembelajaran dalam Meningkatkan Minat Siswa - Wendha Adha Juliasnyah; Nunuk Suryani; Leo Agung Sutimin (Universitas Sebelas Maret, 2016)
This research aimed to find out: (1) how was the condition of instructional process in mathematics in five grade of SD Muhmmadiyah 1 Ngawi, (2) the suitable developmental procedure of Flipbook as a multimedia for mathematics in SD Muhammadiyah 1 Ngawi, (3) the effectiveness of Flipbook in increasing students’ motivation. This research designed in Research and Development study design corridor with procedures; (1) analyzing the needs needed in developing the Product, (2) designing prototypical product, (3) developing the product, (4) implementing the product in the field, and (5) evaluating product’s weaknesses. In addition, this study used totally 52 samples. 26 samples in experimental group (five graders in Billal Bin Robbah class) and 26 samples in control group (five graders in Khadijah Binti Kubro class). Furthermore, in collecting the data, the researcher used questionnaire and achievement test as the instruments and it was analyzed using Descriptive statistic methods and ttest. After Administering the data analyses, it was found that: (1) the category of the product was good based on the means of points given by Content Expert-4, 74; (2) the category of the product was good based on the means of points given by Media Experts-4, 66), (3) the product considered very good based on first field test with means of 4, 67 or 78% ; (4) the product also considered very good based on second field test with means of 4, 57 or 91%; (5) H1 was accepted, means that achievement of the two groups was different shown by the means (Experimental Group-72,38 and Control Group-63.83). The result of the t-test was interpreted based on parameter; t DK= ???? ???? < −1.706 ???????? ???? > 1.706 and t obs =8.048 Ɇ DK